An analysis on the use of Warren's distal splenorenal shunt surgery for the treatment of portal hypertension at the University Hospitals Leuven. Issue 4 (4th July 2021) - Van Praet, Karel M.; Ceulemans, Laurens J.; Monbaliu, Diethard; Aerts, Raymond; Jochmans, Ina; Pirenne, Jacques
Abstract: Introduction: Extrahepatic portal vein thrombosis (PVT) is the most common cause of portal hypertension (PH), particularly in children. PH-related manifestations include refractory variceal bleeding, splenomegaly and ascites. Albeit more rarely performed, the distal splenorenal shunt (Warren's shunt) has proven to be effective in selectively decompressing the collateral circulation. The aim of our study was to describe our experience with the distal splenorenal shunt and to determine the long-term effect on PH-related side-effects. Methods: Distal splenorenal shunt operations performed at our institution between 2000 and 2014 were reviewed for: age, male/female ratio, children/adults ratio, body mass index, indications, grade of PVT (Yerdel classification), maximal shunt-flow velocity, shunt patency and thrombosis, re-intervention for variceal bleeding and survival. Complications of PH (esophageal variceal bleeding and ascites) were compared pre- versus post-operatively (last follow-up). Paired student t -test and fisher's exact were applied for pre- versus post-operative comparison. Results are reported as median [range]. Results: Fourteen patients with PVT and refractory complications of PH underwent distal splenorenal shunt surgery. Age was 15 years [4.5–66]. Male/female ratio was 7/7. PVT -grade was 2 [1–4]. Follow-up was 3 [0.5–14]. All shunts were patent (100%) with no shunt thrombosis (0%) at last follow-up. There was no re-intervention for variceal bleeding (0%) and survival at last follow-up was 100%. Occurrence of esophageal variceal bleeding was higher pre-operatively (57%) than postoperatively (0%) ( p  = .0032) and also the incidence of ascites was higher pre-operatively (79%) than postoperatively (0%) ( p  < .0001). Conclusions: Based on our experience, the distal splenorenal shunt can be considered a valuable surgical technique for PVT-induced PH, with excellent post-operative prevention of complications of PH.